Involvement of the TGF-β Signaling Pathway in the Development of YAP-Driven Osteosarcoma Lung Metastasis - Morice, Sarah; Danieau, Geoffroy; Tesfaye, Robel; Mullard, Mathilde; Brion, Régis; Dupuy, Maryne; Ory, Benjamin; Brounais-Le Royer, Bénédicte; Corre, Isabelle; Redini, Françoise; Verrecchia, Franck (Frontiers in Oncology, 2021)
Background: The poor survival rate of patients with osteosarcoma (OS) specifically with metastases at diagnosis undergoes the urgency to develop new therapeutic strategies. Although we recently demonstrated the key role of YAP/TEAD signaling in the growth of OS primary tumor the molecular mechanisms by which YAP regulates metastases development remain poorly understood. Methods: The molecular mechanisms by which YAP regulates metastases development were studied using overexpression of mutated forms of YAP able or not to interact with TEAD. Molecular signatures were identified using RNA-sequencing analysis and genes set enrichment. Interactions between YAP and Smad3 were studied using PLA, immunoprecipitation and promoter/specific gene assays. Involvement of the TGF- pathway in the ability of YAP to stimulate metastatic development in vivo was studied using an inhibitor of the TGF-β cascade in a preclinical model of OS and in vitro on the ability of OS cells to migrate and invade. Results: Our work shows that a high YAP expression is associated with the presence of lung metastases which predicts a poor prognosis. Molecular analysis indicates that the TGF-β signaling is involved in YAP-driven osteosarcoma cell pro-migratory phenotype, epithelial mesenchymal transition, cell migration and in vivo lung metastases development. Regardless of its ability to bind to TEAD, YAP interacts with Smad3 and stimulates the transcriptional activity of TGF-β/Smad3, thereby enhancing the ability of TGF-β to stimulate lung metastases development. Conclusions: We demonstrated the crucial involvement of the TGF-β/Smad3 signaling pathway in YAP-driven lung metastatic development in OS.